DARIUS I (522–486 BCE) AND THE CONSOLIDATION OF HIS POWER THROUGH THE CONSTRUCTION OF THE APADANA PALACE IN SUSA - Kalthuma Abdul Wahid (گۆڤارا زانستێن مرۆڤایەتی یا زانكۆیا زاخۆ, 2025)
The Apadana Palace (The Palace of Assemblies) was built by the order of Darius I of the Achaemenid Empire in 521 BC in the city of Susa, the capital of Elam. Unlike other kings, Darius left behind the greatest number of inscriptions and writings, a deliberate strategy to reinforce his authority—particularly since he came to power through a coup. The construction of this palace held considerable significance: it served to demonstrate the king’s power and dominance, especially after he successfully suppressed revolts and expanded his empire to include a vast array of regions and diverse peoples. The architectural art of the Achaemenid period—especially as seen in the Apadana—reflects the participation of various peoples across the empire, with strong influences from Median architectural styles and craftsmanship. This study aims to analyze the inscriptions and reliefs of King Darius discovered in the Apadana Palace, thereby shedding light on the development of Achaemenid art and the consolidation of Darius I’s power.